Implementasi Model Pendidikan Karakter Berbasis Disiplin Barak dalam Membentuk Kepribadian Siswa SMA - Sartika, Dian; Zulaikha, Siti; Mayasari, Linda Ika (Proceeding of Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2025)
This study aims to analyze the implementation of a barracks-based character education model in shaping student personality in senior high schools (SMA). This model was developed by adapting the principles of discipline, responsibility, and independence applied in the barracks or dormitory system, with the hope of developing students with integrity and strong personalities. The research method used was descriptive qualitative with a case study approach. Data were collected through observation, in-depth interviews with teachers and students, and documentation of character education activities within the school environment. The results indicate that the implementation of the barracks-based character education model has a positive impact on student personality development, particularly in aspects of time discipline, adherence to rules, and the ability to cooperate and respect others. Furthermore, the habituation of structured activities such as morning assembly, group activities, and daily evaluations has been shown to increase students' sense of responsibility and leadership. However, challenges remain in the consistency of implementation and family support, which is not fully aligned with the school's disciplinary values. Overall, this study confirms that the barracks-based character education model is an effective strategy for fostering strong, independent, and character-based personalities in high school students and can serve as a reference for other educational institutions in designing sustainable character development systems.